(untitled) (University Journal of Zoology, Rajshahi University, 2012)
An investigation was conducted to study the abundance and diversity of Small Indigenous Species (SIS) of fish in the Chalan Beel. Sampling was carried out frequently over a year in selected landing centres, fish markets and catch points. A total of 82 SIS fish belonging to 10 orders, 22 families and 46 genera were recorded. The order Cypriniformes (42.68%) was the most dominant order comprising 35 species. The most dominant family of the order Cypiniformes was Cyprinidae (77.14%) comprising 27 species, and Puntius was the largest genus including 7 species. The most abundant SIS fishes observed during the study period were Tengra (Mystus vittatus, M. tengara), Punti (Puntius sophore and P. ticto), Taki (Channa punctatus), Guchi Baim (Mastacembelus pancalus), and the least abundant SIS fish were Aplocheilus panchax, Badis badis, Danio sp. and Chaca chaca. Availability of the species were ranked as Few (39%), followed by Common (23%), Very Common (15%), Rare (16%) and Very Rare (7%). At Mohisluti fish landing centre (under Tarash, Sirajganj) the highest number of species (79, 96.34%) of small fishes were found. Abundance of different SIS fishes were found to vary with the season. DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10756 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 67-72